The Role of Good Corporate Governance in Predicting Carbon Emissions at Mining Companies - Pikar Setiawan; Sri Iswati; Raden Roro widya Ningtyas Soeprajitno (AKUNTANSI DEWANTARA, 2019)
The main objective of this study was to examine the role of Good Corporate Governance on Carbon Emission Disclosure in mining companies listed on the Indonesia Stock Exchange from 2013 to 2017. The data used were 65. Using tools STATA 14 and testing hypothesis using linear regression with a significance level of 5%. The F test indicates a stable and significant model. R square is 39,26% indicating there are other variables that can affect the model by 60,74%. The results of the study show that there are one variables that have proven to have no significant effect on Carbon Emissions, namely variabel Gender diversity. This research proves that the gender diversity does not afflect the commitment to disclose carbon emission. On the other hand, this research also supports argument about board size and board independent. On the other hand, this research proves that there are four variable that have a significant effect on disclosure of carbon emissions in mining companies, namely Foreign diversity, Independent comissioner, Independent director and Board size. This result means supporting Kilic and Kuzey, (2019); Nasih et al., (2019) and Ben-amar et al., (2017) .